Real-world prescription patterns for reproductive assistance patients in China: A trend analysis from 2016 to 2020 - Jin, Jing; Zhu, Jialei; Tang, Jing (Frontiers in Pharmacology, 2022)
Background: Assisted reproductive technology (ART) is one of the main treatments for patients with Infertility. Although many studies on the treatment of ART have been published, there is no unified conclusion on the choice of drug treatment in China. Our goal is to investigate the actual drug treatment mode of reproductive assistance patients in China, focusing on the trend and rationality of sex hormone use in the past five years. Method: We conducted a cross-sectional analysis of the data from the hospital prescription analysis cooperation project supervised by the China Medical Association. Results: Among 225225 patients included in this study, the top three cities were Guangzhou, Shanghai and Zhengzhou. The average age is 32.99 years old, and 60.38% of women are between 25 and 34 years old. The main therapeutic drugs taken were mainly hormone drugs. There were 11 kinds of main therapeutic drugs. The top five were urotropin for injection, different progesterone preparations. The varieties and proportion of injections are the most according to the statistics of outpatient drugs in key cities of China, including the most common forms of ovulation induction and urotropia, triptorelin, and progesterone. Within 5 years, although the total dosage of urotropin was the highest, it showed a downward trend. The dosage of progesterone and didroxyprogesterone showed an upward trend, among which progesterone showed the fastest upward trend. Conclusion: The average age of patients has not increased significantly, while the opportunity cost of women's childbirth has increased, which seriously hinders the realization of childbearing intention. The overall medication selection is reasonable. The dosage of first-line urotropin and chorionic gonadotropin recommended by the guidelines is also high, but the dosage of oral first-line treatment of ovarian stimulation in unexplained infertility is low, and the dosage of progesterone is gradually increasing. Some drugs will increase the economic burden of patients. On the premise of meeting the clinical needs, how to further improve the level of rational drug use in outpatients and realize the economic, safe and effective use of drugs, so as to reduce the economic burden of patients will be the focus of future work.